2015
DOI: 10.1108/ilds-06-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

CARL Libraries – a Canadian resource-sharing experience

Abstract: Purpose – This study aims to map the current resource-sharing environment in Canada through the lens of its research libraries in general and the University of Alberta in particular. The findings present an interesting view of changing resource sharing patterns and trends. Design/methodology/approach – Interlibrary loan (ILL) transaction data were compiled from annual data reported to the Canadian Association of Research Libraries (CARL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These results are at odds with Webster and Moyo (2016), and Dean (2017) who suggested that the usage of ILL increased because of the convergence of the three events. However, these results are at variance with Kelsall and Onyszko (2010), Raubenheimer and Van Niekerk (2015), Panda and Mallappa (2015), De Jong and Frederiksen (2015), Foran, (2015a), Stapel (2016), Yi (2016), Chalhoub (2017) who determined that ILL requests in Canada, South Africa, India and Netherlands declined but at odds with Fraser et al (2011) who noticed a substantial increase at a university in the Caribbean. Further, the results are at variance with Kilpatrick and Preece (1996), Calvert and Fleming (2013) and Nash and McElfresh (2016) in that the budget cuts do not seem to have a substantial effect on ILL activities.…”
Section: Findings and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These results are at odds with Webster and Moyo (2016), and Dean (2017) who suggested that the usage of ILL increased because of the convergence of the three events. However, these results are at variance with Kelsall and Onyszko (2010), Raubenheimer and Van Niekerk (2015), Panda and Mallappa (2015), De Jong and Frederiksen (2015), Foran, (2015a), Stapel (2016), Yi (2016), Chalhoub (2017) who determined that ILL requests in Canada, South Africa, India and Netherlands declined but at odds with Fraser et al (2011) who noticed a substantial increase at a university in the Caribbean. Further, the results are at variance with Kilpatrick and Preece (1996), Calvert and Fleming (2013) and Nash and McElfresh (2016) in that the budget cuts do not seem to have a substantial effect on ILL activities.…”
Section: Findings and Discussionmentioning
confidence: 85%
“…Yi (2016) concluded that the decrease was because of the proliferation of open access journals and institutional repositories (IRs) in Korea and globally. Other studies reported decreased use of ILL services (De Jong and Frederiksen, 2015; Foran, 2015a, Chalhoub, 2017). These studies also attributed the decreased demand for ILL services to open access journals and IRs.…”
Section: Literature Reviewmentioning
confidence: 92%
“…It has wide applications in natural language processing. It is necessary to convert a document to a vector, namely, mapping the documents (de Jong and Frederiksen, 2015) in the vector space, then use the vector calculation to compute the distance between the vectors. Generally speaking, the key to establish VSM is to determine the dimension, which is known as an item.…”
Section: Vector Space Modelmentioning
confidence: 99%
“…Canadian resource sharing is viewed through the prism of the Canadian Association Research Libraries and a case study of ILL at the University of Alberta. The crucial role of the Canadian National Site Licensing Project in the decline of ILL requesting in 2005 is identified and there is much of interest -especially perhaps in comparing and contrasting the experience of its big neighbour -the USA, (de Jong and Frederiksen, 2015).…”
Section: Resource Sharingmentioning
confidence: 99%